Skin Health in Dance Focusing on Professional Dance and Latin American Formation Dance during Periods of Different Training Loads - Eileen M. Wanke; Olga L. Zimmermann; Mike Schmidt; Daniela Ohlendorf; Alexandra Wallner; Tanja Fischer (Applied Sciences, 2022)
Up to the present, there has been a lack of studies on the skin health of professional and recreational dancers. Dancers are at risk of skin diseases due to contact with allergenic or irritating substances and working in humid environments. The aim of the present study was, therefore, to examine skin health in two different dance styles and training periods. Methods: Physical dermatological examination of professional dancers (PD; n = 35) and Latin American formation dancers (LD; n = 79) after a 4-week period of recovery (T0) and a period of high training or work load (T1). Results: PD are significantly more frequently affected by skin dermatoses than LD (T0, p = 0.004) (frontal traction alopecia, hair loss, facial seborrhoea, xerosis cutis of the trunk and extremities, and facial folliculitis). The following significant differences between the sexes were observed in the LD: more folliculitis of the trunk in male subjects (T0 and T1, p = 0.009), more frequent xerosis cutis of the extremities (p < 0.001) and perioral dermatitis in female subjects (T1, p = 0.043). Subjects with skin lesions trained more frequently, performed more times per year, and had longer dance experience. Discussion: Based on the findings, preventive measures for skin protection (especially informing dancers about skin health) are necessary. At the same time, further studies on this topic are important.